Perception students on teaching and learning using Google Classroom among FPTV student - Tan, King Hiyang; Abd Rani, Nurnasiha Annisa; Zakariah, Siti Hajar (Penerbit UTHM, 2021)
The Malaysian Education Development Plan recommends higher education institutions to empower online learning at a global level (Ministry of Education Malaysia, 2015). The use of information and communication technology (ICT) such as Learning Management System (LMS) will create a creative and conducive learning environment that will change the teaching and learning process (Halili, 2016). It will enhance the quality on teaching and learning process between students and lecturers at the university. Nowadays, various Learning Management System (LMS) applications was exist and used in schools as well as in educational institutions because this application can improve the quality of teaching and learning process and interaction between students and lecturers at the University (Sedana & Wijaya , 2010). This app such as Google Classroom is often used in educational institutions in Malaysia or abroad. By using Google Classroom application in teaching and learning should be enhanced in educational field access to improve quality.